The Effect of Coloring Mandalas on Depression, Anxiety and Stress in Elderly People Referred to Daily Rehabilitation Center for the Elderly in Tehran: A Clinical Trial - Parisa Ahmadi; Nasrin Alaee; Mahshid Foroughan (Iran University of Medical Sciences, 2023)
Background & Aims According to the statistics, the number of older people in Iran is increasing. Considering the occurrence of major changes in old age and the high prevalence of stress, anxiety, and depression in the elderly, this study aims to examine the effect of coloring mandala patterns on depression, anxiety, and stress of older people in Tehran, Iran. Materials & Methods This is a quasi-experimental, single-group study (clinical trial) with a pre-test/post-test design. Participants were 40 older people referred to Yas Elderly Day Care Center in Tehran in 2021 who met the entry criteria and were selected non-randomly. They were asked to color the mandala patterns in 20 minutes (using colored pencils) for 4 consecutive weeks, two sessions per week. Their anxiety, depression, and stress were measured by the depression, anxiety, and stress scale-21 items (DASS-21) before and immediately after the intervention. The data were analyzed in SPSS software, version 23. Results Of 40 participants, 57.5% were women, 65% were married, and 67.5% had a diploma or higher education. Their mean age was 72.03±5.34 years. Data analysis showed that coloring mandalas significantly reduced depression (P=0.001), anxiety (P=0.001), and stress (P=0.001). Conclusion Coloring mandala designs can reduce the depression, anxiety, and stress of the elderly. Therefore, this method can be used as a simple and affordable method to improve the mental health of the elderly.